Preliminary Critical P-limit Values of 0.01 M CaCl2 Soil Test Procedure - Jászberényi, István; Loch, Jakab (Acta Agraria Debreceniensis, 2001)
In the last decade, the 0.01 M CaCl2 extraction procedure was tested as a multi-nutrient extractant. In 1995-97, international joint research activities were carried out within the COPERNICUS project. Detailed calibration of conventional and the 0.01 M CaCl2 extraction procedures for pH, Mg and K were published. The amount of phosphorus extracted using a 0.01 M CaCl2 solution is very low and reflects the intensity parameter of phosphorus bio-availability. As a readily desorbed P fraction of soils can reflect the soil P-supply and the CaCl2-P values are in close correlation with P-fertiliser rates and P balance. However, the effects of various soil characteristics on CaCl2-P values are different and their interpretation is difficult. Relatively poor correlations were found between amounts of P extracted by conventional and CaCl2 soil test methods and, therefore, P limit values could not be calculated directly. To characterise the soil P supply at different sites, the CaCl2 desorbed P and the adsorbed P in a modified Baker Soil Test were also applied. Soil test results of Hungarian long-term fertiliser experiments and recommended CaCl2-P limit values, calculated on yield effects and soil characteristics, are discussed.